Environment-friendly powder coating for improving groove powdering as well as preparation method and application of environment-friendly powder coating
By selecting appropriate polyester resin and hydroxyalkyl amide in the HAA coating system and controlling the particle size of the powder coating, the problem of poor powder performance on the groove of the HAA coating system is solved, and a high groove powder coefficient and good coating coverage effect are achieved.
Patent Information
- Application Number
- CN202311041024.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-17
- Publication Date
- 2025-02-25
AI Technical Summary
The existing HAA coating system has poor powder performance on grooves, which is difficult to approach the level of TGIC coating system, affecting the service life and beauty of the workpiece.
By selecting a polyester resin with an acid value between 20-27 and a hydroxyalkyl amide to match it, and controlling the particle size of the powder coating to be between 34-42 μm, an environmentally friendly powder coating with a high groove powder coefficient was prepared.
The high groove powder coefficient (≥0.5) of the HAA coating system at different groove depths is achieved, which is close to the level of the TGIC coating system, and the coating covering effect and appearance and performance of the workpiece are improved.
Smart Images

Figure CN119505651A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmentally friendly powder coatings, and specifically comprises an environmentally friendly powder coating for improving powdering of grooves, a preparation method and application thereof. Background Art
[0002] In daily production and life, building profiles, home appliance housings, shelves and other products need to be coated with protective coatings on the surface to increase their service life. Since these workpieces have grooves and dead corners of a certain depth, the sprayed protective coating cannot cover all areas well, which will affect the service life and appearance of the workpiece. Therefore, how to accurately spray cover all grooves and dead corners and improve the powder coating on the grooves has become a technical problem.
[0003] Due to the continuous tightening of national environmental protection, powder coatings as a VOC-free environmentally friendly coating are gradually replacing traditional oil / water-based coatings. At present, TGIC is mostly used as a curing cross-linking agent for powder coatings on the market, and is used in combination with film-forming resins to improve the defects of powdering on grooves. CN108129961B discloses a coating that uses TGIC as a curing agent, and is used in combination with polyester resin SJ4ET and polyester resin SJ9006 to improve the powdering performance of workpiece grooves. The patent selects suitable raw materials and raw material ratios, and sets a suitable dosage range, so that the powdering rate of the groove of the TGIC system powder coating reaches 60%. However, TGIC is not only toxic, but also expensive.
[0004] Hydroxyalkylamide (HAA) is a cheap and environmentally friendly powder curing agent that has been widely used in developed countries in recent years. However, due to its high reactivity and strong hydrophilicity, water will be produced during the reaction, resulting in its groove powdering performance being worse than that of the TGIC coating system. Therefore, it is of great significance to improve the groove powdering performance of the HAA coating system. However, there are relatively few research reports in this direction, and it is urgent to develop more HAA coating systems with high groove powdering performance. Summary of the invention
[0005] In view of the above problems existing in the prior art, the first object of the present invention is to provide an environmentally friendly powder coating that improves the powder coating of the groove. The coating obtained by using the powder coating has a high powder coating coefficient of the groove (≥0.5), which is close to the level of the TGIC coating system, and solves the problem of low powder coating coefficient and poor performance of the current HAA coating system. At the same time, it avoids the adverse effects on the appearance and performance of the substrate caused by poor powder coating of the coating groove.
[0006] The second object of the present invention is to provide a method for preparing the environmentally friendly powder coating as described above.
[0007] The third object of the present invention is to provide an environmentally friendly coating prepared using the environmentally friendly powder coating as described above.
[0008] To achieve the above first object, the technical solution adopted by the present invention includes:
[0009] The present invention discloses an environmentally friendly powder coating for improving the powdering of grooves. The powder coating comprises 50-70 parts by weight of polyester resin;
[0010] 2-3 parts of hydroxyalkylamide;
[0011] 3-5 parts of additives;
[0012] Wherein, the acid value of the polyester resin is 20-27.
[0013] Further, the polyester resin includes but is not limited to
[0014] YC9018 produced by Anhui Yongchang New Materials Co., Ltd. has an acid value of 23-26;
[0015] and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd., with an acid value of 20-26;
[0016] And / or SJ5101 produced by Anhui Shenjian New Materials Co., Ltd., with an acid value of 23-27.
[0017] Further, the polyester resin is selected from 60-70 parts by weight of YC9018 produced by Anhui Yongchang New Materials Co., Ltd. or SJ5101 produced by Anhui Shenjian New Materials Co., Ltd.
[0018] Further, in parts by weight, the polyester resin comprises
[0019] 15-30 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.;
[0020] 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd.
[0021] Further, in parts by weight, the polyester resin comprises
[0022] 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.;
[0023] 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd.
[0024] Further, in parts by weight, the polyester resin comprises
[0025] 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.;
[0026] 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd.
[0027] Furthermore, the powder coating further comprises, by weight, 2-21 parts of pigment and 2-20 parts of filler.
[0028] Furthermore, the pigment is selected from carbon black and / or titanium dioxide; and the filler is selected from barium sulfate.
[0029] To achieve the above second purpose, the technical solution adopted by the present invention includes:
[0030] The present invention discloses a method for preparing the powder coating as described above, comprising the following steps:
[0031] 50-70 parts of polyester resin, 2-3 parts of hydroxyalkylamide and 3-5 parts of auxiliary agent are uniformly premixed, melt-extruded through an extruder at an extrusion temperature of 90-120°C, and then cooled by the extruder roller. The extruded flakes are crushed and sieved to obtain a powder coating product with a particle size of 34-42μm.
[0032] To achieve the third objective, the technical solution adopted by the present invention includes:
[0033] The invention discloses an environmentally friendly coating prepared by using the powder coating as described above.
[0034] Furthermore, the powder coating is applied on the outer surface of the workpiece having the groove to form a coating.
[0035] Furthermore, the coating is prepared according to the following steps:
[0036] The powder coating is sprayed on the outer surface of the workpiece while maintaining the outer surface temperature of the workpiece not lower than 0°C, and then baked at 175-185°C for 5-15 minutes.
[0037] Furthermore, when the groove depth of the coating is ≤10 cm, the groove powder coating coefficient is not less than 0.5.
[0038] Furthermore, when the groove depth of the coating is ≤15 cm, the groove powder coating coefficient is not less than 0.5.
[0039] Beneficial effects of the present invention:
[0040] The present invention selects suitable polyester resin and hydroxyalkylamide for combination, controls the amount of each component in the powder coating and the particle size of the powder coating, so that the obtained coating has a higher groove powder coating coefficient. When the groove depth is ≤10cm, the groove powder coating coefficient is not less than 0.5, which is close to the level of the TGIC coating system, and solves the problems of low groove powder coating coefficient and poor performance of the current HAA coating system, and avoids many adverse problems caused to the workpiece due to insufficient groove powder coating. At the same time, the powder coating of the present invention also has the advantages of low cost, non-toxicity, environmental protection, etc., which is conducive to the better promotion and use of the HAA coating system. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0042] Figure 1 The process flow chart of the present invention for preparing powder coating is shown. DETAILED DESCRIPTION
[0043] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] In the prior art, reports on improving the powder coating performance of grooves are mainly concentrated on the TGIC coating system. Considering the toxicity and cost of TGIC, it is hoped to use the more environmentally friendly and low-cost HAA to replace TGIC. However, due to the low groove powder coating coefficient and poor performance of the current HAA coating system, and the TGIC coating system and the HAA coating system are two completely different systems, there is no reference value in the selection of formula ingredients. Therefore, the use of the HAA coating system to improve the powder coating performance of grooves is still a relatively blank field. To this end, the inventors have screened out a polyester resin that is suitable for the HAA system and can meet the application requirements of groove powder coating through a large number of experimental studies. The specific formula is: by weight, the powder coating comprises
[0045] 50-70 parts of polyester resin;
[0046] 2-3 parts of hydroxyalkylamide;
[0047] 3-5 parts of additives;
[0048] Wherein, the acid value of the polyester resin is 20-27.
[0049] According to experiments, when the acid value of the selected polyester resin is within the specified range of the present invention, after being used in combination with the hydroxyalkylamide curing agent, the obtained HAA powder coating formula can be sprayed on a workpiece with a groove under the control of a specific particle size (34-42um), which can improve the groove powder coating coefficient (0.5-0.7) of the HAA powder coating at different groove depths, making it close to the level of the TGIC coating system, effectively solving the current HAA coating system The problem of low groove powder coating coefficient and poor performance, at the same time, avoids the adverse effects on the appearance and performance of the substrate caused by poor powder coating on the coating groove.
[0050] During the experiment, it was also found that when the polyester resin is selected from one or more of YC9018 (acid value of 23-26), YC9501D (acid value of 20-26) produced by Anhui Yongchang New Materials Co., Ltd. and SJ5101 (acid value of 23-27) produced by Anhui Shenjian New Materials Co., Ltd., it can effectively exert the compounding effect with hydroxyalkyl amide and improve the groove powder coating coefficient of the coating.
[0051] In a specific embodiment, when the polyester resin is a single component, the polyester resin contains 60-70 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd. or SJ5101 produced by Anhui Shenjian New Materials Co., Ltd., and the obtained HAA coating system has a groove powder coating coefficient of not less than 0.5 when the groove depth is ≤10 cm.
[0052] In a specific embodiment, when the polyester resin is a multi-component, the polyester resin comprises 15-30 parts by weight of YC9018 produced by Anhui Yongchang New Materials Co., Ltd., 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd., and the obtained HAA coating system has a groove powder coating coefficient of not less than 0.5 when the groove depth is ≤10cm; preferably, when the polyester resin comprises 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd., 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd., the obtained HAA coating system has a groove powder coating coefficient of not less than 0.5 when the groove depth is ≤10cm, and can take into account the national standard (GB / T 1865-2009) for aging requirements; more preferably, when the polyester resin contains 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd. and 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd., the groove powder coating coefficient will be higher, which can ensure that the groove powder coating coefficient of the obtained HAA coating system is not less than 0.5 when the groove depth is ≤15cm, and the formed paint film has good leveling appearance, while taking into account the aging requirements in the national standard (GB / T 1865-2009).
[0053] Furthermore, the hydroxyalkylamide is selected from T-105 produced by Huangshan Huahui Technology Co., Ltd.
[0054] Furthermore, the powder coating also contains 2-21 parts of pigment and 2-20 parts of filler; illustratively, the pigment is selected from carbon black produced by Shanghai Cabot Chemical Co., Ltd. and / or titanium dioxide ATR-312 produced by Anhui Anada Titanium Co., Ltd.; the filler is selected from barium sulfate produced by Shanghai Bangyi Trading Co., Ltd.
[0055] Further, by weight, the auxiliary agent comprises
[0056] Leveling agent 0.1-1 part;
[0057] Benzoin 0.1-0.5 parts;
[0058] Brightener 0.1-1 part;
[0059] Degassing agent 0.1-0.5 parts;
[0060] Anti-yellowing agent 0.1-1 part;
[0061] 0.1-0.5 parts of wax powder.
[0062] In a specific embodiment, the leveling agent is selected from GLP588 produced by Ningbo Nanhai Chemical Co., Ltd.; the manufacturer of the benzoin is Ningbo Nanhai Chemical Co., Ltd.; the brightener is selected from BLC701 produced by Ningbo Nanhai Chemical Co., Ltd.; the degassing agent is selected from HA500 produced by Huangshan Huahui Technology Co., Ltd.; the anti-yellowing agent is selected from W5036 produced by Suzhou Patna Environmental Protection New Materials Co., Ltd.; the wax powder is selected from PEW-0300 produced by Nanjing Tianshi New Materials Technology Co., Ltd.
[0063] The present invention also provides a method for preparing the powder coating as described above, comprising the following steps:
[0064] 50-70 parts of polyester resin, 2-3 parts of hydroxyalkylamide, 3-5 parts of additives, 2-21 parts of pigments and 2-20 parts of fillers are uniformly premixed, melt-extruded through an extruder at an extrusion temperature of 90-120°C, and then cooled by an extruder roller. The extruded flakes are crushed and sieved using a 160-250 mesh screen to obtain a powder coating product with a particle size of 34-42μm.
[0065] It should be noted that during electrostatic spraying, the powder coating rate mainly depends on the amount of charge on the powder particles, and the charge on the powder is proportional to the square of the particle size of the powder particles. Increasing the particle size can increase the charge on the powder to a certain extent, thereby increasing the coating rate. However, the particle size of the powder particles cannot be too large. If the particle size is too large, the gravity of the large particles will exceed the aerodynamic force and electrostatic force. During the flight, the powder coating will fall due to gravity before reaching the surface of the workpiece, which will reduce the coating rate. If the powder is too fine, the charge will be reduced, and the coating construction efficiency will decrease. Ultrafine powder is basically not charged, and too fine powder also increases the difficulty of powder production. Based on this, the particle size of the powder coating needs to be strictly controlled, and the particle size should be set to 34-42μm.
[0066] In a specific embodiment, the electrostatic spraying conditions can refer to the conventional spraying conditions in the art, for example, the air pressure can be 0.08-0.12MPa, the voltage can be 50-75KV, and the spraying distance can be 130-170mm. Those skilled in the art can adjust according to actual conditions.
[0067] In a specific embodiment, the present invention provides three workpieces to be coated with different groove depths (5 cm, 10 cm, and 15 cm) for testing, and spraying is performed and the powder coating coefficient of the groove after spraying the paint is detected according to the method provided in the literature (Coatings and Protection, 2021, 42(07):17-23).
[0068] Example 1
[0069] This embodiment provides an environmentally friendly powder coating for improving powder coating on grooves, comprising the following components in parts by weight, see Table 1.
[0070] Table 1 Coating formula raw materials table of Example 1
[0071]
[0072] This embodiment also provides a method for preparing the powder coating as described above, comprising the following steps:
[0073] The two polyester resins, hydroxyalkylamide, additives, pigments and fillers are uniformly premixed, melt-extruded through an extruder at an extrusion temperature of 90-120°C, cooled by the extruder roller, and the extruded flakes are crushed and sieved using a 160-250 mesh screen to obtain a powder coating product with a particle size of 34-42μm.
[0074] Comparative Examples 1-4
[0075] The formula raw material table of Comparative Examples 1-4 is shown in Table 2, and the preparation process of the powder coating is shown in Example 1.
[0076] Table 2: Raw materials of coating formula of comparative examples 1-4
[0077]
[0078]
[0079] Note: The acid value of SJ5701 produced by Anhui Shenjian New Materials Co., Ltd. is 29-35.
[0080] Table 3 Spraying conditions of Example 1 and Comparative Examples 1-4
[0081] Group Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Air pressure(MPa) 0.1 0.1 0.1 0.1 0.06 Voltage(KV) 60 60 60 60 60 Spraying distance (mm) 150 150 150 150 150
[0082] Table 4 Test results of Example 1 and Comparative Examples 1-4
[0083]
[0084] Embodiment 2-4
[0085] This embodiment provides an environmentally friendly powder coating for improving the powder coating of grooves, comprising the following components in parts by weight, see Table 5, and the preparation process of the powder coating is shown in Example 1.
[0086] Table 5: Raw materials for coating formulations of Examples 2-4
[0087]
[0088]
[0089] Comparative Examples 5-10
[0090] The formula raw material table of Comparative Examples 5-10 is shown in Table 6, and the preparation process of the powder coating is shown in Example 1.
[0091] Table 6: Raw materials of coating formulas for comparative examples 5-9
[0092]
[0093] Note: The acid value of SJ5701 produced by Anhui Shenjian New Materials Co., Ltd. is 29-35.
[0094] Table 7 Spraying conditions of Examples 2-4 and Comparative Examples 5-9
[0095]
[0096] Table 8 Test results of Examples 2-4 and Comparative Examples 5-9
[0097]
[0098]
[0099] Example 5
[0100] This embodiment provides an environmentally friendly powder coating for improving powder coating on grooves, comprising the following components in parts by weight, see Table 9, and the preparation process of the powder coating is shown in Example 1.
[0101] Table 9: Raw materials of coating formula of Example 5
[0102]
[0103] Comparative Examples 10-13
[0104] The formula raw material table of Comparative Examples 10-13 is shown in Table 10, and the preparation process of the powder coating is shown in Example 1.
[0105] Table 10: Raw materials of coating formula of comparative examples 10-13
[0106]
[0107]
[0108] Note: The acid value of SJ5701 produced by Anhui Shenjian New Materials Co., Ltd. is 29-35.
[0109] Table 11 Spraying conditions of Example 5 and Comparative Examples 10-13
[0110] Group Example 5 Comparative Example 10 Comparative Example 11 Comparative Example 12 Comparative Example 13 Air pressure(MPa) 0.1 0.1 0.1 0.1 0.06 Voltage(KV) 60 60 60 60 60 Spraying distance (mm) 150 150 150 150 150
[0111] Table 12 Test results of Example 5 and Comparative Examples 10-13
[0112]
[0113] Subsequently, the coatings obtained by spraying the coating compositions of Examples 1-5 were subjected to xenon lamp aging tests. The results are shown in Table 13.
[0114] Table 13 Xenon lamp aging test results of Examples 1-5
[0115]
[0116] From the data in Tables 1-13, it can be found that by selecting a polyester resin with an acid value that meets the specified conditions, the prepared coating can have a higher groove powder coating coefficient (≥0.5) at different groove depths. However, when the polyester resin contains YC9501D, although it can meet the application requirements of the groove powder coating coefficient, there may be a risk of poor appearance leveling.
[0117] In order to ensure the comprehensive performance of the coating in terms of gloss, appearance, impact resistance, aging, etc., it is advisable to control the amount of YC9018 (20-25 parts), and use it in combination with SJ5101 (25-45 parts). This not only further improves the groove powder coating coefficient of the coating, but also maintains the comprehensive performance of the coating in terms of gloss, appearance, impact resistance, aging, etc., solves the problem of low groove powder coating coefficient and poor performance of the current HAA coating system, and avoids many adverse problems caused by insufficient groove powder coating to the workpiece.
[0118] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A powder coating for improving the powdering of grooves, characterized in that: The powder coating comprises 50-70 parts by weight of polyester resin; 2-3 parts of hydroxyalkylamide; 3-5 parts of additives; Wherein, the acid value of the polyester resin is 20-27.
2. The powder coating according to claim 1, characterized in that The polyester resin comprises YC9018 produced by Anhui Yongchang New Materials Co., Ltd. has an acid value of 23-26; and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd., with an acid value of 20-26; And / or SJ5101 produced by Anhui Shenjian New Materials Co., Ltd., with an acid value of 23-27.
3. The powder coating according to claim 2, characterized in that In parts by weight, the polyester resin contains 60-70 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd. or SJ5101 produced by Anhui Shenjian New Materials Co., Ltd.
4. The powder coating according to claim 2, characterized in that The polyester resin comprises 15-30 parts by weight of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.; 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd.; Preferably, the polyester resin comprises, by weight: 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.; 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd. and / or YC9501D produced by Anhui Yongchang New Materials Co., Ltd.; More preferably, the polyester resin comprises, by weight 20-25 parts of YC9018 produced by Anhui Yongchang New Materials Co., Ltd.; 25-45 parts of SJ5101 produced by Anhui Shenjian New Materials Co., Ltd.
5. The powder coating according to claim 1, characterized in that: The powder coating further comprises 2-21 parts of pigment and 2-20 parts of filler by weight; Preferably, the pigment is selected from carbon black and / or titanium dioxide; and the filler is selected from barium sulfate.
6. The method for preparing a powder coating according to any one of claims 1 to 5, characterized in that: The steps include: 50-70 parts of polyester resin, 2-3 parts of hydroxyalkylamide and 3-5 parts of auxiliary agent are uniformly premixed, melt-extruded through an extruder at an extrusion temperature of 90-120°C, and then cooled by the extruder roller. The extruded flakes are crushed and sieved to obtain a powder coating product with a particle size of 34-42μm.
7. An environmentally friendly coating, characterized in that: The powder coating is obtained by electrostatic spraying according to any one of claims 1 to 5.
8. The environmentally friendly coating according to claim 7, characterized in that: The powder coating is sprayed on the outer surface of the workpiece having the grooves to form a coating.
9. The environmentally friendly coating according to claim 7, characterized in that: The coating is specifically prepared according to the following steps: The powder coating is sprayed on the outer surface of the workpiece while maintaining the outer surface temperature of the workpiece not lower than 0°C, and then baked at 175-185°C for 5-15 minutes.
10. The environmentally friendly coating according to claim 8, characterized in that: When the groove depth of the coating is ≤10cm, the powder coating coefficient of the groove is not less than 0.5; Preferably, when the groove depth of the coating is ≤15 cm, the groove powder coating coefficient is not less than 0.5.
Citation Information
Patent Citations
Coatings for improving powder coating performance in workpiece grooves, their preparation methods, and applications
CN108129961B